Pharmacological activity of aromatic plants from the region contrasted with the traditional use of the population to Pucara district - Junchaya Yllescas, Vilma Amparo (2020)
The objective of the present research was to analize the pharmacolcogical activity of the aromatic plants of the region contrasted with the traditional use of  population of the districto of Pucara. Concluding that only 25% of the population of Pucara maintains the use of the aromatic plants of the region conserving their traditions, while 75% prefer other plants.